Praktik Akad Wakalah pada BMT Amanah Bersama Bojonegoro Perspektf Hukum Islam - Nabillah Febri Annisa; Nabrina Nur Zeninda; Nadya Fatma Kholili; Rosa Novitasari Aisyah; Ulil Alai (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
This article discusses the practice of wakalah contracts at BMT Amanah with Bojonegoro. This research is field research. Data collection was carried out through interviews, observation, and documentation. The collected data were analyzed deductively. Baitul Mal wat Tamwil (BMT) is a micro institution that is operated on the principle of profit-sharing, growing, and developing micro-business to elevate the degree and dignity and defend the interests of the poor. In the BMT Amanah Bersama, the most frequently used financing is the murabahah contract but still does not rule out other contracts such as the wakalah contract. The wakalah contract at BMT Amanah Bersama does not stand alone, but from the wakalah contract, the BMT can receive income earned through ujrah (fees) which is used as a reciprocal between the BMT institution and the customer so that both are mutually beneficial. Based on this practice, the wakalah contract carried out at BMT Amanah Bersama is by the principles of Islamic law.